2007
DOI: 10.1002/pssb.200743026
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic‐to‐ferromagnetic transition induced by aluminum in the Ti(Fe1−xAlx)2 intermetallic compounds: a 57Fe Mössbauer spectroscopy study

Abstract: PACS 71.20. Lp, 75.25.+ z, 76.80.+ y Mössbauer spectroscopy has been used to investigate the hyperfine field distributions and the local spin configurations of Fe atoms in the magnetically ordered Ti(Fe 1-x Al x ) 2 compounds. The evolution of the spin arrangement of the Fe atoms was observed over the concentration range 0 ≤ x ≤ 0.25 at 5 K. The Al impurity suppresses the ferromagnetic exchange in the Fe(6h) layers and simultaneously provides the conditions for a transition of the Fe(2a) atoms, which are nonma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The concentration dependence of the /QSHS provides information about the rotation of the Fe(6h) magnetic moments on the average. In the HfFe 2 compound with a collinear FM structure, QSH is equal to +0.053(5) mm/s, suggesting that the magnetic moments are aligned parallel to the hexagonal c-axis [12,15]. In the (Hf 1Àx Ti x )Fe 2 compounds, as the Ti concentration increases, the /QSH(6h)S value increases rapidly.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The concentration dependence of the /QSHS provides information about the rotation of the Fe(6h) magnetic moments on the average. In the HfFe 2 compound with a collinear FM structure, QSH is equal to +0.053(5) mm/s, suggesting that the magnetic moments are aligned parallel to the hexagonal c-axis [12,15]. In the (Hf 1Àx Ti x )Fe 2 compounds, as the Ti concentration increases, the /QSH(6h)S value increases rapidly.…”
Section: Discussionmentioning
confidence: 92%
“…For TiFe 2 , the spectrum consists of the magnetic subspectrum (6h sites, B hf ¼ 9.70(3) T) and quadrupole doublet (nonmagnetic 2a sites). The parameters of the hyperfine interactions for 57 Fe in TiFe 2 have been previously considered in detail [15]. In particular, it was shown that the principal component of the EFG tensor lies in the basal plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation